القيم الانسانية في مجتمع الصحابة - الشيخ بالحاج, قاسم بن أحمد (العالمية للطباعة والخدمات, 2016)
Keywords: Zanzibar

مذكرات أميرة عربية - بن ساطان, سالمة بنت السيد سعيد (وزارة التراث والثقافة, 2016)
Keywords: Zanzibar

Islamic Law, Gender, and Social Change in Post-Abolition Zanzibar - Kapteijns, Lidwien (Islamic Africa, 2016)
Keywords: Recension; Zanzibar

Islamic Law, Gender, and Social Change in Post-Abolition Zanzibar, written by Elke E. Stockreiter, 2015 - Stiles, Erin E. (Islamic Law and Society, 2016)
Keywords: Recension; Zanzibar

Islamic Law, Gender, and Social Change in Post-Abolition Zanzibar, written by Elke E. Stockreiter - McMahon, Elisabeth (Journal of Religion in Africa, 2016)
Keywords: Recension; Zanzibar

“The Ignorant Do Not Belong to Any Particular Sect”: Legal Practice and Social Identities in Colonial Zanzibar - Stockreiter, Elke E. (Islamic Law and Society, 2016)
Omani and British reforms of Zanzibar’s judiciary date back to the 1820s, when the abolition of the slave trade justified Western control of the sultanate’s political economy. The sultan enacted the abolition of slavery as a legal status in 1897, seven years after Zanzibar had become a British protectorate. Through the lens of a 1948 inheritance case, I analyze how colonial judicial reforms shaped the negotiation of grievances and the judges’ interpretations of social equality. As members of the colonial elite, both Muslim and British judges were embedded in a racialized social hierarchy. Their reasoning not only exposes the continuous marginalization of former slaves but also attests to ex-slaves’ ability to assert material power. While a Muslim and a British judge used different hermeneutics, both validated the marriage of a Hadrami water carrier to a former slave, thereby affirming his entitlement to a share of his wife’s estate.
Keywords: Zanzibar

Cracks in the dome: fractured histories of empire in the Zanzibar Museum, 1897-1964 - Longair, Sarah (Routledge, 2016)
Keywords: Zanzibar

Taarab music in Zanzibar in the twentieth century: a story of 'old is gold' and flying spirits - Topp Fargion, Janet (Routledge, 2016)
Keywords: Zanzibar